Reversal of senescence-associated beta-galactosidase expression during in vitro three-dimensional tissue-engineering of human chondrocytes in a polymer scaffold - Shojiro Katoh (Nature Portfolio, 2021)
Abstract Regenerative medicine applications require cells that are not inflicted with senescence after in vitro culture for an optimal in vivo outcome. Methods to overcome replicative senescence include genomic modifications which have their own disadvantages. We have evaluated a three-dimensional (3D) thermo-reversible gelation polymer (TGP) matrix environment for its capabilities to reverse cellular senescence. The expression of senescence-associated beta-galactosidase (SA-βgal) by human chondrocytes from osteoarthritis-affected cartilage tissue, grown in a conventional two-dimensional (2D) monolayer culture versus in 3D-TGP were compared. In 2D, the cells de-differentiated into fibroblasts, expressed higher SA-βgal and started degenerating at 25 days. SA-βgal levels decreased when the chondrocytes were transferred from the 2D to the 3D-TGP culture, with cells exhibiting a tissue-like growth until 42–45 days. Other senescence associated markers such as p16INK4a and p21 were also expressed only in 2D cultured cells but not in 3D-TGP tissue engineered cartilage. This is a first-of-its-kind report of a chemically synthesized and reproducible in vitro environment yielding an advantageous reversal of aging of human chondrocytes without any genomic modifications. The method is worth consideration as an optimal method for growing cells for regenerative medicine applications.